2021
DOI: 10.3390/nano11061411
|View full text |Cite
|
Sign up to set email alerts
|

Optical Constants and Structural Properties of Epitaxial MoS2 Monolayers

Abstract: Two-dimensional layers of transition-metal dichalcogenides (TMDs) have been widely studied owing to their exciting potential for applications in advanced electronic and optoelectronic devices. Typically, monolayers of TMDs are produced either by mechanical exfoliation or chemical vapor deposition (CVD). While the former produces high-quality flakes with a size limited to a few micrometers, the latter gives large-area layers but with a nonuniform surface resulting from multiple defects and randomly oriented dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 55 publications
(67 reference statements)
0
16
0
Order By: Relevance
“…The study of sensitivity enhancement with vdW materials has become a hot topic in the last decade, since they are promising both as immobilization layers [ 13 , 14 , 15 , 16 , 17 ] and as optical sensitivity enhancing layers [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Furthermore, additional layers of graphene or other materials can protect the metal from the environment, thereby improving the stability of the sensor structure [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The study of sensitivity enhancement with vdW materials has become a hot topic in the last decade, since they are promising both as immobilization layers [ 13 , 14 , 15 , 16 , 17 ] and as optical sensitivity enhancing layers [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Furthermore, additional layers of graphene or other materials can protect the metal from the environment, thereby improving the stability of the sensor structure [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…We employed a two-layer optical model for ellipsometry data analysis: quartz substrate with SnS 2 or SnSe 2 film with the thickness determined from AFM ( Figure 3 e,i). Similar to other TMDCs [ 52 , 53 ], we describe SnS 2 and SnSe 2 dielectric function by the Tauc–Lorentz oscillator model (see Methods) [ 54 , 55 ]. Figure 3 a,b shows the resulting optical constants n and k for SnS 2 and SnSe 2 films.…”
Section: Resultsmentioning
confidence: 99%
“…However, it was noticed that MBE provides greater control on the epitaxial registry in both cases. Recently, Ermolaev et al 106 have presented a detailed study on the structural and optical properties of a monolayer of MoS 2 thin films grown by MBE on sapphire. The analysis has shown that the MBE-grown MoS 2 film exhibits a two-fold greater quantum yield of PL and lower photobleaching when compared with the CVD-synthesized MoS 2 films (Fig.…”
Section: Recent Advances In Mbe-grown Transition Metal Dichalcogenidesmentioning
confidence: 99%